2015
DOI: 10.1246/cl.150204
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Feature in Hybrid Perovskite CH3NH3PbBr3 Single Crystals

Abstract: We have measured the temperature dependence of the reflection and photoluminescence spectra of a lead bromide hybrid material (CH 3 NH 3 PbBr 3 ) using high-quality macroscopic single crystals. Single crystals provide clear and sampleindependent reflection spectra that permit discussion of the properties of the photoexcited carriers. We have found that excitons still exist in CH 3 NH 3 PbBr 3 , even at room temperature. We have also determined the temperature dependence of the exciton resonance energy and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 27 publications
11
58
0
Order By: Relevance
“…27), MAPbBr 3 (refs 52, 53), CsPbBr 3 (refs 54, 55) as 13 meV, 18 meV and 16 meV, respectively, by taking into account both the experimental and theoretical estimations performed before and also the band structure we presented in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…27), MAPbBr 3 (refs 52, 53), CsPbBr 3 (refs 54, 55) as 13 meV, 18 meV and 16 meV, respectively, by taking into account both the experimental and theoretical estimations performed before and also the band structure we presented in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…The bulk parameters ε b = 4.7, [73] ℏγ = 5.9 × 10 −2 eV, and ℏω T = 2.303 eV [74] were taken from literature value. The bulk parameters ε b = 4.7, [73] ℏγ = 5.9 × 10 −2 eV, and ℏω T = 2.303 eV [74] were taken from literature value.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a study on point defects in MAPbBr 3 [19] showed that the materials' performances are highly tolerant to defect formation, suggesting that stable defects may induce shallow levels in the band gap. Kunugita et al [20] recently investigated the excitonic properties of these compounds as a function of temperature. The study revealed that electron-hole pairs remain bound even at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In this study the photoluminescence line broadening with temperature was attributed to exciton-phonon interaction. An evaluation of the coupling between the exciton and the longitudinal optical (LO) phonon [20] resulted in the frequency of the LO phonon being estimated to be ω LO = 16.8 ± 2.4 meV (135 ± 20 cm −1 ). Hence, it appears that the dynamic of the MA and FA molecules crucially impacts the optical and electronic properties of this class of materials.…”
Section: Introductionmentioning
confidence: 99%